A green in situ synthesis of silver nanoparticles on cotton fabrics using Aloe vera leaf extraction for durable ultraviolet protection and antibacterial activity. Issue 19 (November 2017) - Zhou, Qingqing; Lv, Jingchun; Ren, Yu; Chen, Jiayi; Gao, Dawei; Lu, Zhenqian; Wang, Chunxia
This study presented a simple and environmentally friendly method of in situ synthesis of silver nanoparticles (AgNPs) on cotton fabrics for durable ultraviolet (UV) protection and antibacterial activity using Aloe vera leaf extraction (AVE) as a reducing and stabilizing agent. Cotton fabrics were pretreated in water, and then immersed in AgNO3 and AVE, respectively. Cotton fabrics were characterized by small angle X-ray diffraction (XRD), scanning electron microscopy (SEM), thermogravimetric analysis, UV protection, antibacterial activity, and laundering durability. Comparing with the smooth surface of the control cotton fabric, SEM and energy dispersive X-ray spectrometry (EDX) results showed that there were a considerable number of Ag2 O and AgNPs loading on the surface of the pretreated and Ag loaded cotton fabrics. The XRD pattern indicated, respectively, the existence of Ag2 O and AgNPs, the structures of which were similar to JCPDS File No.65-3289 and JCPDS File No. 01-071-4613 on the pretreated and Ag loaded cotton fabrics. The pretreated and Ag loaded cotton fabrics showed excellent UV protection, antibacterial activity, and laundering durability, especially the Ag loaded cotton fabric, of which the UV protection factor value and transmission of UVA were 148 and 1.11%, respectively, after 20 washing cycles, and the clear zone width was more than 4 mm against E. coli or S. aureus . AgNPs facilitated the improvement of the thermal property of the cotton fabrics. Thus this facile in situ reduction of AgNPs with AVE may bring a promising and green strategy to produce functional textiles.